Effect of Screen-Time on Sleep Pattern and Dietary Habits among College-Going Students in COVID-19 Pandemic - Saxena, Rahul; Parmar, Nitesh; Kaur, Prabhleen; Allen, Tanu (Indian Journal of Community Health, 2021)
Background: Optimum and good quality of sleep are pertinent to the health and equilibrium of biological functions. Increased use of electronic gadgets for academics and social interactions during the COVID-19 pandemic has extended the screen time of students, affecting sleep and eating patterns. Aim & Objective: To study the association of extended screen time on sleep pattern and calorie intake among college students during the COVID-19 pandemic. Settings and Design: Observational study was conducted using ‘Google forms’ to collect data on sleep and food intake among 60 college-going students. Methods and Material: Google form composed of questions related to demographic, anthropometry, screen time, sleep quality (PSQI) & dietary pattern (food frequency questionnaire) and tied to written consent was sent via WhatsApp to college students. Statistical analysis used: Data were grouped based on the screen time >10 hrs and </=10 hrs/day. Independent “t” test, Chi-square test and Mann Whitney test were used to compare the sleep domains scores and calorie intake. Results: With an average screen time of 10.9 hrs, 38% of students were using the screen maximally during the night. Poor Sleep Quality was (PSQI Score>5) observed in 80% of the college students, with 46.6% having a sleep of <5 hrs/day. Students' calorie intake was ten times the recommended daily requirement during the stay at home but was negatively related to screen-time, though non-significant. Conclusions: The study concludes that average screen time of students of age group 18-24 years have increased during night under the lockdown. This extended viewing in night has shifted the sleep circadian cycle to morning hours, with daytime sleepiness and poor sleep quality. The high calorie intake was also observed in students during lockdown though no correlation was established with the screen time and sleep quality.